Analysis of the Influence of Thyroid Nodule Characteristics on the Results of Shear Wave Elastography - Xue, Ji-ping; Kang, Xiao-yan; Miao, Jun-wang; Zhang, Yan-xia; Li, Hui-zhan; Yao, Fu-cheng; Kang, Chun-song (Frontiers in Endocrinology, 2022)
Objective To analyze the ultrasonic characteristics of false-negative and false-positive results of shear wave elastography (SWE) in the diagnosis of thyroid nodules to clarify the influence of nodular characteristics on SWE and to guide the clinical application of SWE. Methods A total of 435 thyroid nodules from 343 patients with the diagnosis confirmed by surgical pathology were analyzed. Preoperative ultrasonography and SWE were conducted. The conventional ultrasound characteristics of thyroid nodules and the maximum Young’s modulus were recorded. The false negativity and false positivity of SWE for the diagnosis of thyroid nodules were calculated. The ultrasonic characteristics of thyroid nodules with SWE false results were analyzed, and logistic regression analysis was adopted to determine the ultrasonic characteristics associated with SWE false results of thyroid nodules. Results Among 323 malignant nodules, the SWE false negativity was 27.2% (88/323). The false positivity of SWE in 112 benign nodules was 19.6% (22/112). Regression analysis showed that an increase in the nodule volume increased the risk of SWE false-positive results (odds ratio [OR] 3.286; 95% confidence interval [CI]: 1.572–6.871; P = 0.002) and decreased the risk of false-negative results (OR 0.238; 95% CI: 0.115–0.493; P < 0.001). Nodules with coarse calcification had an increased risk of SWE false-positive results compared with those without calcification (OR 5.303; 95% CI: 1.098–25.619; P = 0.038). However, nodules with scattered hyperechoic foci had a reduced risk of SWE false-negative results (OR 0.515; 95% CI: 0.280–0.951; P = 0.034). Conclusion Nodular size and calcification were correlated with SWE false results, and the clinical application of SWE should be combined with conventional ultrasound features. Fine needle aspiration or a puncture biopsy should be conducted if necessary.